Analisis Daya Dukung Tanah Lapisan Pondasi Jalan pada Proyek Jalan Tol Tebing Tinggi – Parapat Tahap I (Zona 1) - Nasrullah, Nasrullah; Lubis, Kamaluddin; Amsuardiman, Amsuardiman (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2024)
In the construction of the Tebing Tinggi-Parapat Toll Road Phase I (Zone 1), the carrying capacity of the soil is very important for the success of construction. The bearing capacity of the soil was tested using DCP and Field CBR tools.  The purpose of this study is to obtain soil carrying capacity based on the results of the Dynamic Cone Penetrometer (DCP) test using the DCP tool and the results of the California Bearing Ratio (CBR) test using the CBR tool on the subgrade soil. Meanwhile, the methods used in this study are SNI, AASHTO T 193 and ASTM D 1883 methods. From the results of the calculation of the DCP test, the average CBR score was 6.16%. And the results of the calculation of the field CBR test obtained a maximum average CBR value of 6.43%. Based on the AASHTO T 193 and ASTM D 1883 methods, it meets the requirements. Because the CBR value obtained is more than 6%. With the average CBR value, it meets the requirements. So the soil does not require compaction and the work can be continued to the landfill work (borrowed material).